2013
DOI: 10.7763/ijssh.2012.v2.137
|View full text |Cite
|
Sign up to set email alerts
|

Purchase Decision of Life Insurance Policies among Malaysians

Abstract: The research objective of this paper is to determine the socio-demographic and economic factors that have significant influence on the demand for life insurance in Malaysia. A hurdle count-data model is used to accommodate the separate decisions on the demand for life insurance which is divided into two parts: whether to purchase a life insurance policy and if so, how many policies to purchase. The results show that there are some slight differences in the factors that determine the decision to purchase life i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 12 publications
3
25
0
1
Order By: Relevance
“…The studies of Baek and DeVaney (2005), Loke and Goh (2012), and Annamalah (2013) showed inconsistent findings. Baek and DeVaney (2005) examined the purchase of term (non-cash value) and cash value life insurance among American households.…”
Section: Risk Attitudesmentioning
confidence: 97%
See 1 more Smart Citation
“…The studies of Baek and DeVaney (2005), Loke and Goh (2012), and Annamalah (2013) showed inconsistent findings. Baek and DeVaney (2005) examined the purchase of term (non-cash value) and cash value life insurance among American households.…”
Section: Risk Attitudesmentioning
confidence: 97%
“…Meanwhile on a different continent, the study by Loke and Goh (2012) examined the purchase of life insurance among Malaysians residing in Penang. Their findings unexpectedly showed that risk averse individuals are less likely to buy life insurance.…”
Section: Risk Attitudesmentioning
confidence: 99%
“…Burnett & Palmer 1984;Ferber & Lee 1980;Gutter & Hatcher 2008;Leary, Kane & Woods 2014). Only a little attention has been paid to the examination of the psychographic characteristics of an individual in motivating him/her in owning life insurance in Malaysia (Annamalah 2013;Loke & Goh 2012;Wan Aris, Sahak & Shaadan 2009). Therefore, this study has been undertaken to include the three commonly examined psychographic characteristics together in one study to empirically examine the significance of the personal value, risk-taking attitude and trusting belief of Malaysian individuals on life insurance ownership.…”
Section: G a L L E Y P R O O Fmentioning
confidence: 99%
“…Risk attitude refers to an individual's preference for risky choices (Wärneryd 1996). Expected utility theory with or without life insurance has been used to explain the decisions of individuals with different risk attitudes in purchasing life insurance (Annamalah 2013;Gutter & Hatcher 2008;Loke & Goh 2012;Tan & Lim 2017). The individual who has decided to purchase life insurance is opting for a certain level of utility over an uncertain level of utility.…”
Section: Risk Attitudementioning
confidence: 99%
“…In addition, life insurance consumption is significantly lower in Islamic nations [34] and Muslim populations [9,29]. However, Loke and Goh [35] (2011) consider ethnicity as the proxy for religion and demonstrate that both Indians and Chinese are inclined to hold life insurance policies compared to Malays. Thus, we expect that the effect of religion on the demand for life insurance varies due to the differences in religious beliefs (In the SHARE questionnaire, there is generalization of questions pertaining to religious participation.…”
Section: Religionmentioning
confidence: 99%